Synergistic impact of pollution from microplastics and glyphosate herbicides on the biophysics of horticultural land with different soil orders in Baso, West Sumatra, Indonesia - Darfis, Irwan; Maulana, Amsar; Harianti, Mimien; Rezki, Dewi; Herviyanti, Herviyanti (Journal of Degraded and Mining Lands Management, 2026)
Increased use of plastic mulch and glyphosate herbicides may lead to synergistic effects on soil properties, particularly in horticultural land. This study examined the synergistic effects of microplastics and glyphosate herbicides on the biophysics of horticultural land across different soil orders in Baso, West Sumatra, Indonesia. Soil sampling followed a quantitative, random survey approach. Sampling testing was conducted using a 2 x 4 factorial randomized block design with three groups. The first factor comprised two different land uses (forest land as a control and horticultural land), and the second factor comprised four soil orders (Entisols, Inceptisols, Ultisols, and Oxisols) at a depth of 0-20 cm. The transition of horticultural land significantly interacted with differences in soil orders in Baso, affecting bulk density, porosity, the sand fraction, and soil enzymatic activity through synergistic effects of microplastic pollution and glyphosate herbicide residues. The main effect of differences in land use between forest and horticultural land was not significant on biophysical properties, but was significant on pollutants. However, the main effect of different soil orders was insignificant for biophysical properties but significant for pollutants, particularly microplastics. The synergistic impact of microplastic pollution was positively related to glyphosate (r = 0.608**; y = 0.0162x + 2.4476; R² = 0.3697), which has the potential to increase pollutant persistence.